Diagnostic value of PET with different radiotracers and MRI for recurrent glioma: a Bayesian network meta-analysis - Qi Meng; Tian Xiaoxue; Wang Yinzhong; Xingru Lu; Junqiang Lei (BMJ Open, 2023)
Objective The purpose of this study was to evaluate the diagnostic accuracy of 6 different imaging modalities for differentiating glioma recurrence from postradiotherapy changes by performing a network meta-analysis (NMA) using direct comparison studies with 2 or more imaging techniques.Data sources PubMed, Scopus, EMBASE, the Web of Science and the Cochrane Library were searched from inception to August 2021. The Confidence In Network Meta-Analysis (CINeMA) tool was used to evaluate the quality of the included studies with the criterion for study inclusion being direct comparison using 2 or more imaging modalities.Data extraction and synthesis The consistency was evaluated by examining the agreement between direct and indirect effects. NMA was performed and the surface under the the cumulative ranking curve (SUCRA) values was obtained to calculate the probability of each imaging modality being the most effective diagnostic method. The CINeMA tool was used to evaluate the quality of the included studies.Main outcomes and measures Direct comparison, inconsistency test, NMA and SUCRA values.Results A total of 8853 potentially relevant articles were retrieved and 15 articles met the inclusion criteria. 18F-FET showed the highest SUCRA values for sensitivity, specificity, positive predictive value and accuracy, followed by 18F-FDOPA. The quality of the included evidence is classified as moderate.Conclusion and relevance This review indicates that 18F-FET and 18F-FDOPA may have greater diagnostic value for glioma recurrence relative to other imaging modalities (Grading of Recommendations, Assessment, Development and Evaluations B).PROSPERO registration number CRD42021293075.